(untitled) (Veterinary Science, 2017)
Transmissible venereal tumor (TVT), also known as infectious sarcoma, venereal granuloma, transmissible lymphosarcoma or Sticker tumor, is a benign reticulo endothelial tumor of the dog that mainly affects external genitalia and occasionally the internal genitalia. Although, TVT has a cosmopolite distribution, it is a highly frequent neoplasia in tropical and subtropical zones. It is commonly found in urban areas with large populations of free-roaming dogs. Small pink to red, 1 to 3 mm diameter nodules can be observed 2 or 3 weeks after transplantation. Initial lesions are superficial dermoepidermical or pedunculated. Then multiple nodules fuse together forming larger red hemorrhagic cauliflower- like friable masses. Definitive diagnose is based on physical examination and typical cytological findings of exfoliated cells. Chemotherapy has shown to be the most effective and practical therapy, being vincristine sulphate the most frequently used drug